2016
DOI: 10.1016/j.jcis.2016.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Rapid carbon nanotubes suspension in organic solvents using organosilicon polymers

Abstract: A strategy for a simple dispersion of commercial multi-walled carbon nanotubes (MWCNTs) using two organosilicones, polycarbosilane SMP10 and polysilazane Ceraset PSZ20, in organic solvents such as cyclohexane, tetrahydrofuran (THF), m-xylene and chloroform is presented. In just a few minutes the combined action of sonication and the presence of Pt(0) catalyst is sufficient to obtain a homogeneous suspension, thanks to the rapid hydrosilylation reaction between SiH groups of the polymer and the CNT sidewall. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…However, results showed that after first 5 min of sonication, the CNT length was decreased around 65% [42] and significant nanotube fragmentation from 15 to 20 min was observed [42,45]. On the other hand, in the same time interval, a stable and homogeneous CNT dispersion could be obtained, remaining practically constant after 15 min of sonication [46,47]. For this work, it was observed a similarity, in which the chosen sonication time was sufficient for the acquisition of homogeneous dispersion with all solvents studied, presenting a very similar appearance with dark and opaque aspects, being the light passage totally blocked.…”
Section: Dispersing Agent Studymentioning
confidence: 99%
“…However, results showed that after first 5 min of sonication, the CNT length was decreased around 65% [42] and significant nanotube fragmentation from 15 to 20 min was observed [42,45]. On the other hand, in the same time interval, a stable and homogeneous CNT dispersion could be obtained, remaining practically constant after 15 min of sonication [46,47]. For this work, it was observed a similarity, in which the chosen sonication time was sufficient for the acquisition of homogeneous dispersion with all solvents studied, presenting a very similar appearance with dark and opaque aspects, being the light passage totally blocked.…”
Section: Dispersing Agent Studymentioning
confidence: 99%
“…A neat PEI film with thickness around 0.1 mm, was obtained by solution mixing process considered the most common technique for processing nanostructured polymer composites. [45] First, 10 g of the polymer (pellets) was dissolved in 250 ml of methylene chloride under stirring for 30 min. Subsequently, the solution was transferred to an aluminum mold with dimensions of (30 × 30) cm and taken to a vacuum oven (Vacucell, model VUK/VU 55) at 40 C for 3 hr to dry the solvent.…”
Section: Composite Processingmentioning
confidence: 99%
“…By comparison, Ceraset PSZ 20 is an attractive silazane precursor with vinyl sidegroups [20]. Both precursors can be thermally crosslinked at temperatures below 100 °C with the addition of peroxide initiators or UV crosslinked with an appropriate photoinitiator [19,21,22]. Liew et al tested three different photoinitiators (Irgacure 651, Irgacure 907, and ITX) to selectively UV crosslink Ceraset and found that a combination of different photoinitiators tended to produce the most perpendicular sidewalls [17].…”
Section: Introductionmentioning
confidence: 99%